Restitution or Cooperation? Competing Visions of Post-Colonial Cultural Development in Africa - Sarah van Beurden (University of Duisburg-Essen, Käte Hamburger Kolleg / Centre for Global Cooperation Research (KHK/GCR21), 2015)
This paper provides a critical and historical perspective on the use of the language of `development cooperation' in characterizations of post-colonial relations between the West and Africa. Using the example of the post-colonial debates over cultural and economic restitution between Congo and its former colonizer Belgium, this paper narrates the historical process by which the post-colonial relations between the two countries became defined as `development cooperation', and the implications of that process. The paper shows that since its political independence in 1960 until the late 1980s, the language in which Congo/Zaire described its `cooperation' with its former Belgian colonizer was one that emphasised restitution, while Belgium insisted on a language of `development cooperation' (ontwikkelingssamenwerking). The paper argues that the prevalence of the use of the development cooperation language today not only obscures the historical process behind its ascent; it also masks inequalities that are deeply characteristic of the post-colonial relations between the two countries.
urn:nbn:de:hbz:464-20160603-064106-3
Keywords: 320; Development; cooperation; restitution; Africa; museums